Beyond the screen : An exploration of theoretical foundations and paradigms in human-computer interface design - Usmani, Usman Ahmad; Usmani, Mohammed Umar (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper delves into the multifaceted landscape of Human-Computer Interface (HCI) design, meticulously exploring the foundational theories and cutting-edge paradigms that form the backbone of the digital user experience. It skillfully synthesizes profound insights gleaned from seminal works, including Norman's cognitive model and Fitts' law, as well as delving into socio-technical theories such as Activity Theory and Distributed Cognition. These collective theories illuminate the intricate tapestry of human cognition, motor control, and the dynamic interactions between individuals, technology, and their environment. Furthermore, this paper rigorously analyzes the frontiers of HCI through emerging paradigms like natural user interfaces and affective computing, underlining the paramount importance of user-centered design principles in fostering empathy, inclusivity, and accessibility. By comprehensively exploring and elucidating the theoretical foundations of HCI, this work aspires to invigorate innovative, user-centric design approaches, thus enriching the future of human-computer interactions and enhancing the overall user experience within the digital realm.